Nurses Functional Empowerment as an Approach to Improving Work Life Quality: A field study at Annaba Public Institution for Neighborhood Health - Ladjailia, Youcef; Charafeddine, Khadidja (Journal of Human Sciences, 2023)
The current study aims to reveal the nature of the relationship between the job empowerment of nurses and the quality of work life in the Public Institution for Neighborhood Health in Annaba, as well as to identify the significance of the differences in the levels of job empowerment and quality of work life according to the difference of sex. In order to answer the hypotheses of the study we have opted for a descriptive approach and the use of the empowerment scale. The study sample consisted of 130 male and female nurses, and the results of the study concluded that there is a significant relationship between job empowerment and quality of work life, and there are significant differences in the level of job empowerment depending on gender.